2015
DOI: 10.1016/j.neuropharm.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine potentiation of methylphenidate-induced gene regulation in striatal output pathways: Potential role for 5-HT1B receptor

Abstract: Drug combinations that include the psychostimulant methylphenidate plus a selective serotonin reuptake inhibitor (SSRI) such as fluoxetine are increasingly used in children and adolescents. For example, this combination is indicated in the treatment of attention-deficit/hyperactivity disorder and depression comorbidity and other mental disorders. Such co-exposure also occurs in patients on SSRIs that use methylphenidate as a cognitive enhancer. The neurobiological consequences of these drug combinations are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 91 publications
(147 reference statements)
2
30
1
Order By: Relevance
“…Previously, we showed such potentiation of gene regulation for increases in opioid peptide expression (dynorphin, enkephalin [24]), as well as for blunting of IEG induction by a cocaine challenge [25]; these were measured within 1 day after the repeated treatment. The present study is the first to demonstrate that such potentiated gene blunting after repeated methylphenidate+fluoxetine treatment endures for at least 2 weeks past the treatment, similar to effects of repeated cocaine treatment [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed such potentiation of gene regulation for increases in opioid peptide expression (dynorphin, enkephalin [24]), as well as for blunting of IEG induction by a cocaine challenge [25]; these were measured within 1 day after the repeated treatment. The present study is the first to demonstrate that such potentiated gene blunting after repeated methylphenidate+fluoxetine treatment endures for at least 2 weeks past the treatment, similar to effects of repeated cocaine treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Such potentiation of methylphenidate-induced gene regulation was first demonstrated for acute induction of immediate-early genes (IEGs; c- Fos, Zif268 ) [21,22] and neuropeptides (substance P, dynorphin) [23]. Further studies showed that fluoxetine also potentiates increases in dynorphin, enkephalin and 5-HT1B receptor expression [24], as well as blunting of IEG induction [25], produced by repeated methylphenidate treatment, in striatal neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The probes had the following sequence: Zif268 ( Egr1 ), complementary to bases 352–399, GenBank accession number M18416; c-Fos , bases 207–254, X06769; Homer1a , bases 1493–1540, AB003726. Hybridization and washing procedures were as reported (Willuhn et al, 2003; Van Waes et al, 2015). The sections were apposed to X-ray film (BioMax MR-2, Kodak) for 5–9 days.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, combining MP with a selective serotonin reuptake inhibitor (SSRI; SERT) antidepressant, such as fluoxetine (FLX) or citalopram, in doses that by themselves have no effect on gene regulation, potentiates MP-induced gene regulation in the striatum (for review, see Van Waes and Steiner, 2015). This potentiating effect was demonstrated for acute induction of immediate-early genes (IEGs) such as Zif268 , c- Fos , and Homer1a by MP (Steiner et al, 2010; Van Waes et al, 2010), as well as for expression of neuropeptides (Van Waes et al, 2015) and blunting (repression; Renthal and Nestler, 2008) of IEG induction (Beverley et al, 2014; Van Waes et al, 2014), after repeated MP+FLX treatment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation